2003
DOI: 10.1016/j.adolescence.2003.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Online computer gaming: a comparison of adolescent and adult gamers

Abstract: Despite the growing popularity of online game playing, there have been no surveys comparing adolescent and adult players. Therefore, an online questionnaire survey was used to examine various factors of online computer game players (n=540) who played the most popular online game Everquest. The survey examined basic demographic information, playing frequency (i.e. amount of time spent playing the game a week), playing history (i.e. how long they had been playing the game, who they played the game with, whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
217
4
24

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(258 citation statements)
references
References 11 publications
13
217
4
24
Order By: Relevance
“…In the current study, significantly more males than females were identified as addicted gamers and social gamers, and significantly more females than males were identified as non-gamers, a pattern that has also been widely reported with problem gambling. This gender divide has been reported elsewhere (Desai et al, 2010;Gentile, Choo, Liau, Sim, Fung, & Koo, 2011;Griffiths et al, 2004b;Lemmens et al, 2009Lemmens et al, , 2011Mentzoni et al, 2011;Padilla-Walker et al, 2010;. Whether or not game choice affected these results is beyond the scope of this paper but, as with gambling, video game manufacturers are becoming aware of the market potential of women gamers and these numbers may change as game designers create and promote games geared toward women and girls.…”
Section: Gender Differencesmentioning
confidence: 98%
See 1 more Smart Citation
“…In the current study, significantly more males than females were identified as addicted gamers and social gamers, and significantly more females than males were identified as non-gamers, a pattern that has also been widely reported with problem gambling. This gender divide has been reported elsewhere (Desai et al, 2010;Gentile, Choo, Liau, Sim, Fung, & Koo, 2011;Griffiths et al, 2004b;Lemmens et al, 2009Lemmens et al, , 2011Mentzoni et al, 2011;Padilla-Walker et al, 2010;. Whether or not game choice affected these results is beyond the scope of this paper but, as with gambling, video game manufacturers are becoming aware of the market potential of women gamers and these numbers may change as game designers create and promote games geared toward women and girls.…”
Section: Gender Differencesmentioning
confidence: 98%
“…Males are also more likely than females to play video games and to score more highly on addicted gaming screens (Dauriat et al, 2011;Griffiths, Davies, & Chappell, 2004a, 2004bLemmens, Valkenburg, & Peter, 2011;Mentzoni et al, 2011;Padilla-Walker, Nelson, Carroll, & Jensen, 2010). Desai, Krishnan-Sarin, Cavallo, & Potenza (2010) reported gender differences between gamers and non-gamers.…”
Section: Gender Differencesmentioning
confidence: 99%
“…[5][6][7][8] Adolescence is a period of rapid psychological maturation and of susceptibility to Internet attraction, 9 and adolescents were found to be particularly vulnerable to the negative health impacts of Internet overuse. [10][11][12] Among the negative health impacts, the relationship between Internet addiction and aggression has been addressed. Ko et al 13 reported that although Internet use may reduce distress by providing immediate rewards and opportunities to engage in different activities, excessive use of the Internet is an important risk factor for aggression.…”
Section: Introductionmentioning
confidence: 99%
“…Research has reported that social interac on, especially within online games, may be an important mo vator for people to ini ally play video games and subsequently maintain a long-term interest in the ac vity (Cole & Griffiths, 2007;. Games also func on as a way to make new friends (Klimmt, Schmid, & Orthmann, 2009) and to consolidate social rela onships through shared gameplay (Griffiths, Davies, & Chappell, 2004;Klimmt et al, 2009). Thus, it was expected that social influences would have a significant impact on gaming me and PGU.…”
Section: Extension To the Tpb: Social Influencesmentioning
confidence: 99%
“…With the development of new gaming console machines and the use of the Internet for gaming, new games were introduced that enable people to play together online. Many different genres and pla orms are available and games are also popular among adults (Griffiths et al, 2003;Griffiths, Davies, & Chappel, 2004). This implies that PGB may also occur among adult gamers.…”
Section: Introduc Onmentioning
confidence: 99%